Long Non-coding RNAs Are Central Regulators of the IL-1β-Induced Inflammatory Response in Normal and Idiopathic Pulmonary Lung Fibroblasts - Hadjicharalambous, Marina R.; Roux, Benoit T.; Feghali-Bostwick, Carol A.; Murray, Lynne A.; Clarke, Deborah L.; Lindsay, Mark A. (Frontiers in Immunology, 2018)
There is accumulating evidence to indicate that long non-coding RNAs (lncRNAs) are important regulators of the inflammatory response. In this report, we have employed next generation sequencing to identify 14 lncRNAs that are differentially expressed in human lung fibroblasts following the induction of inflammation using interleukin-1b (IL-1b). Knockdown of the two most highly expressed lncRNAs, IL7AS and MIR3142HG, showed that IL7AS negatively regulated IL-6 release whilst MIR3142HG was a positive regulator of IL-8 and CCL2 release. Parallel studies in fibroblasts derived from patients with idiopathic pulmonary fibrosis showed similar increases in IL7AS levels, that also negatively regulate IL-6 release. In contrast, IL-1b-induced MIR3142HG expression and its metabolism to miR-146a, was reduced by 4- and 9-fold in IPF fibroblasts, respectively. This correlated with a reduced expression of inflammatory mediators whilst MIR3142HG knockdown showed no effect upon IL-8 and CCL2 release. Pharmacological studies showed that IL-1b-induced IL7AS and MIR3142 production and release of IL-6, IL-8 and CCL2 in both control and IPF fibroblasts were mediated via an NF-kB-mediated pathway. In summary, we have catalogued those lncRNAs that are differentially expressed following IL-1-activation of human lung fibroblasts, shown that IL7AS and MIR3142HG regulate the inflammatory response and demonstrated that the reduced inflammatory response in IPF fibroblast is correlated with attenuated expression of MIR3142HG/miR-146a.